2020
DOI: 10.1371/journal.pone.0243102
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma release assay tests are associated with persistence and completion of latent tuberculosis infection treatment in the United States: Evidence from commercial insurance data

Abstract: Background Risk-targeted testing and treatment of latent tuberculosis infection (LTBI) is a critical component of the United States’ (US) tuberculosis (TB) elimination strategy, but relatively low treatment completion rates remain a challenge. Both treatment persistence and completion may be facilitated by diagnosing LTBI using interferon gamma release assays (IGRA) rather than tuberculin skin tests (TST). Methods We used a national sample of administrative claims data to explore associations diagnostic test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…A previous study found that patients at an urban HIV clinic were 1.5 times more likely to receive care adherent to TB treatment guidelines after the clinic transitioned to using an IGRA 29. Another study found being tested with an IGRA to be significantly associated with treatment completion 34. Findings such as ours highlight the potential benefit of IGRAs for patients at-risk of not returning for TST reading.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…A previous study found that patients at an urban HIV clinic were 1.5 times more likely to receive care adherent to TB treatment guidelines after the clinic transitioned to using an IGRA 29. Another study found being tested with an IGRA to be significantly associated with treatment completion 34. Findings such as ours highlight the potential benefit of IGRAs for patients at-risk of not returning for TST reading.…”
Section: Discussionsupporting
confidence: 49%
“…29 Another study found being tested with an IGRA to be significantly associated with treatment completion. 34 Findings such as ours highlight the potential benefit of IGRAs for patients at-risk of not returning for TST reading. Interpretation of LTBI test results can be challenging and may ultimately impact likelihood of providers recommending and patients subsequently initiating treatment.…”
Section: Open Accessmentioning
confidence: 53%
“…Plasma-based cfDNA assay testing offers a new pathway for PTB diagnosis. Although plasma-based testing such as the interferon gamma release assay may provide indirect evidence of PTB without showing evidence of MTB [ 43 ], plasma-based cfDNA testing can provide direct evidence of MTB. Plasma specimens are easily accessible and widely applicable.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that uptake and completion may be influenced by testing. For example, data from the US suggests that individuals tested with IGRA had increased rates of preventive therapy completion compared to those tested with TST [21]. However, it is also possible that testing may reduce uptake if there is a delay between testing and availability of test results.…”
Section: Discussionmentioning
confidence: 99%